India as an emerging power - Ganguly, Sumit (London ; Portland, OR : Frank Cass, 2003)
These essays examine India's relations with key powers including the Russian Federation, China and the USA and with key adversaries in the global arena in the aftermath of the Cold War. One positive relationship is that of India's relations with Israel since 1992.
Introduction / Sumit Ganguly -- The US-India courtship / Robert M. Hathaway -- India, Pakistan, and Kashmir / Stephen Philip Cohen -- Toward a 'Force-in-Being' : the logic, structure, and utility of India's emerging nuclear posture / Ashley J. Tellis -- Asymmetrical Indian and Chinese threat perceptions / John W. Garver -- Indo-Russian strategic relations : new choices and constraints / Deepa Ollapally -- The Indo-French strategic dialogue : bilateralism and world perceptions / Jean-Luc Racine -- India and Israel : emerging partnership / P.R. Kumaraswamy -- The political economy of India's second-generation reforms / Sunila Kale.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: India -- Foreign relations -- 1984-; National security -- India; Inde -- Relations extérieures -- 1984-; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; National security; India; Since 1984